Interactive Whiteboard as a Medium for Nahwu Learning: Bridging Technology and Arabic Grammar Education - Masnun; Segaf Baharun; Sultan Abdus Syakur (Postgraduate of IAIN Metro Lampung Indonesia, 2025)
People who have mastered Nahwu often struggle to adjust to using technology. This research investigates the integration of Interactive Whiteboards (IWBs) as a transformative tool in Nahwu (Arabic syntax) learning, addressing the longstanding challenges associated with traditional pedagogical approaches. The study emphasizes the unique contribution of IWBs in bridging the gap between traditional Nahwu instruction and technology-based learning by incorporating multimodal strategies, such as dynamic diagrams, real-time feedback, and interactive sentence-building exercises. These features not only enhance student engagement but also simplify the comprehension of intricate grammatical rules, making Nahwu more accessible to modern learners. The qualitative research involved 30 students and 5 educators from an Islamic boarding school, utilizing interviews, focus group discussions, classroom observations, and document analysis. Key findings demonstrate that IWBs significantly improve cognitive retention, student participation, and the overall effectiveness of Nahwu instruction. Practical recommendations include providing robust teacher training on IWB integration, designing interactive lesson plans tailored to the needs of Generation Z learners, and leveraging IWB capabilities to foster collaborative and inquiry-based learning environments. This study highlights IWBs as a cornerstone in modernizing Arabic grammar education, offering actionable insights for educators and institutions aiming to implement technology-driven teaching solutions effectively.